Profile and History of the Petu Dondo Dance as an Intangible Cultural Heritage in Tolitoli - Windi; Haliadi; Suyuti; Misnah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The results of this study aim to examine the history of dance, identify the profiles of creators and dancers, and analyze the process of submitting the petu dondo dance as an intangible cultural heritage. The method used is descriptive qualitative. The results of this study indicate that: the history of the petu dondo dance was created by two local artists, namely H. Simon Ismail Tonggolipu and Siti Rahmatia A, Md. Kep in 1992 to be performed at the cultural week in the framework of the anniversary of the Tolitoli Regency. The petu dondo dance as a local cultural heritage that has important historical and cultural values for the Dondo community but has not been widely documented academically or administratively and has not been registered as an Intangible Cultural Heritage (WBTB). In conclusion, the petu dondo dance is a traditional art work originating from Tinabogan Village, Dondo District, Tolitoli Regency, which was created in 1992. The petu dondo dance was created to be performed at the cultural week in the framework of the anniversary of the region and has not been designated as an Intangible Cultural Heritage (WBTB).